Les communes nouvelles des Mauges et la réorganisation politique locale (département de Maine-et-Loire) - Assiba Benoîte Ohoussa; Christine Margetic (L'Espace Politique)
Both on a small and on a large scale, the political geography has changed significantly in France particularly since the 2010's. Many authors show this reshaping of territories (Bideau, 2019; Grison, 2016). In this paper, it is understood as a political process aimed at modifying spatial organization (Vanier, 2002). An age-long concern, it results from the existence of communal fragmentation, which is tried to be reduced. Thus, the "failure" of the 1971 Loi Marcellin and the failure to achieve the objectives of rationalisation and simplification of action (considered by the law relating to the Territorial Administration of the Republic in 1992) compelled the legislator to launch into the 2010 RCT law (Territorial Communities Reform). As a result, from this reform to the 2019 Gatel law, the French municipality map has evolved, with the creation of 774 new municipalities (CN) gathering more than 2,500 historic municipalities (CH) at the end of 2018. These gatherings are very heterogeneous and unevenly distributed on a national scale, with an average of 3.4 founding municipalities. A real silent revolution (Pasquier, 2017) in urban and rural areas, the CNs have the particularity of being initiated by local elected officials. This last point raises an issue, and especially the local political reorganization that they involve and the associated stakes. What are the reasons that push the elected representatives to create the CN, and what discourses do they mobilize? Among the departments concerned by this movement, Maine-et-Loire, in the west of France, is an emblematic example, including the Mauges territory, a community of conurbations organised around 6 CNs as early as 2015, instead of 6 public institutions for inter-municipal cooperation. Answering these questions from this territory led to a major survey between April 2018 and May 2019. The mayors of the 6 CNs and 63 deputy mayors were systematically offered semi-directive face-to-face or telephone interviews which were all transcribed. While the issues of reshaping were at the heart of the interview, which lasted an average of one hour, other problems were also discussed relating to territorial specificities, the future of the delegated municipalities and local governance. In addition, 800 questionnaires were carried out with municipal councillors, residents and local authority staff in order to identify the reality of CNs and the way in which the actors project themselves in such entities. The various answers highlight a certain degree of satisfaction despite the brutality of the change. CNs manage to meet current needs in terms of territorial dynamics. They can nevertheless be a source of tension, going as far calling into question the identity of the municipalities, or even having delegated mayors resign. However, generally speaking, a consensus is emerging. The CN is not challenged because it is deemed necessary. The appeasement will come from power sharing and decision making by those who hold the power, in this Mauges territory where working together and gathering together are asserted values. Ultimately, in spite of important advances, the communal work site remains open, with change opportunities towards territories relevant for action.